Soil quality and crop productivity under 34 years old long-term rainfed rice based cropping system in an Inceptisol of sub-tropical India - Biswas, Sunanda; Singh, Priya; Rahaman, Riaj; Patil, Kalyani V.; De, Nirmal (Frontiers in Soil Science, 2023)
Soil quality deterioration with the introduction of modern agriculture is a major threat to agricultural sustainability and food security and the problem is more aggravated specially under rainfed agriculture. Asessment of soil quality is a tortuous task as it can not be measured directly. The objective of the present investigation was to evaluate the effect of long-term fertilization and manuring on soil quality and identify the most sensitive indicators of assessing soil quality under rainfed rice based system. For this purpose soil samples were collected from selected six treatments viz. control, 100%NPK, 50%NPK, 50%FYM, 100%FYM and 50%NPK+FYM of 34 years old long-term fertilizer experiment with rainfed rice-lentil cropping system situated at BHU Varanasi, India. Result revealed that continuous organic manure application along with inorganic fertilizer significantly influenced all physical, chemical and biological properties of soil. Principal component analysis (PCA) was done to screen out key indicators and mean weight diameter, available Fe, available N, potentially mineralizable N, available Zn, FDA hydrolase activity and Clay were selected as key indicators of soil quality. The highest soil quality index (SQI) of 0.95 was found in 50% NPK+FYM treatment. Regression analysis showed better agreement of equivalent rice yield and SQI (0.87). Therefore, the balanced fertilization with organic and inorganic is important for sustainability of the rainfed rice-lentil cropping system and this practice may be recommended for rainfed rice based system of Indian Inceptisol.